The Effectiveness of Si Sagu (Teacher Academic Supervision System) in Academic Supervision Process for Teachers at 3T Area - Herry Sanoto; Mila Chrismawati Paseleng; Dani Kusuma (Journal of Innovation in Educational and Cultural Research, 2022)
The purpose of this study was to determine the effectiveness of the SI SAGU Academic Supervision (Information System for Teacher Academic Supervision) model in the academic supervision process in the 3T (Foremost, Outermost, Disadvantaged) area in Bengkayang Regency, West Kalimantan Province. The research method used in this research is a quantitative research method by testing the SI SAGU Academic Supervision model used in the academic supervision process in the 3T area. The research subjects in this study were teachers, principals, and school supervisors in Bengkayang Regency. The instruments used in the study were practical questionnaires and interview guidelines. The instrument used has gone through validation and testing by expert validators, so it is feasible to be used in the research process. The data collection technique in this study was documentation of the results of observations, then giving a perception questionnaire to the SAGU SI users consisting of teachers, school principals, and school supervisors. The results showed that the Teacher Academic Supervision Management Information System (SI SAGU) was effectively used in the academic supervision process in the 3T area, namely Bengkayang Regency. Through SI SAGU, the supervision process can be carried out even though there are some geographical constraints and access to each school. The findings in this study are the effectiveness of the application of SISAGU in the 3T area in the academic supervision process, supported by the active participation and enthusiasm of all relevant stakeholders, namely teachers, schools, principals, school supervisors, and the education office.